Mapping the future for research in emergency medicine palliative care: A research roadmap. (4th June 2022) - Aaronson, Emily L.; Wright, Rebecca J.; Ritchie, Christine S.; Grudzen, Corita R.; Ankuda, Claire K.; Bowman, Jason K.; Kuntz, Joanne G.; Ouchi, Kei; George, Naomi; Jubanyik, Karen; Bright, Leah E.; Bickel, Kathleen; et al.
Abstract: Background: The intersection of emergency medicine (EM) and palliative care (PC) has been recognized as an essential area of focus, with evidence suggesting that increased integration improves outcomes. This has resulted in increased research in EM PC. No current framework exists to help guide investigation and innovation. Objective: The objective was to convene a working group to develop a roadmap that would help provide focus and prioritization for future research. Methods: Participants were identified based on clinical, operation, policy, and research expertise in both EM and PC and spanned physician, nursing, social work, and patient perspectives. The research roadmap setting process consisted of three distinct phases that were time staggered over 12 months and facilitated through three live video convenings, asynchronous input via an online document, and a series of smaller video convenings of work groups focused on specific topics. Results: Gaps in the literature were identified and informed the four key areas for future research. Consensus was reached on these domains and the associated research questions in each domain to help guide future study. The key domains included work focused on the value imperative for PC in the emergency setting, models of care delivery, disparities, and measurement of impact and efficacy. Additionally, the group identified key methodological considerations for doing work at the intersection of EM and PC. Conclusions: There are several key domains and associated questions that can help guide future research in ED PC. Focus on these areas, and answering these questions, offers the potential to improve the emergency care of patients with PC needs.